Citra Merek terhadap Kepercayaan Konsumen pada Keunggulan Produk Kosmetik MS GLOW - Rkt, Lana Sari; Hanifah, Nur; Nst, Anggun Dwi Nanda; Nadila, Nurhaida; Nainggolan, Annisa Erina; Ramadhani, Izky Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this research is to find out the level of consumer confidence in the beauty product MS GLOW, which has a significant impact. This shows that customers consider MS GLOW beauty products to be superior to other competing brands. According to customers, products from the MS GLOW brand have high quality and have a positive effect on the face when used. The explanation of the relationship or influence between consumer confidence, brand loyalty, and brand image, with brand loyalty revealed that the business world is always evolving over time, especially in the cosmetics or beauty industry, which has become a necessity for all humans, both men and women. The marketing communication strategy in this research begins with a marketing strategy based on the four Ps, namely product, price, place, and promotion. This research uses a qualitative approach to explain the collected data.